KINERJA PENDAMPING DESA DAN PENDAMPING LOKAL DESA DALAM MENDAMPINGI PENGELOLAAN DANA DESA DI KECAMATAN ABANG - Alvi Yasin, Mohammad Fauzi; Yudharta, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2019)
ABSTRACT This study focuses on the performance of Village Facilitators and Local Village Facilitators who served in Abang, Karangasem District. The performance is the level of achievement of one's work in carrying out its responsibilities in accordance with the objectives set. Someone's performance can be used as a reference and measure of success in carrying out their duties and responsibilities. There are 6 indicators used in assessing the performance of Village Facilitators and Local Village Facilitators in Abang District, including quality, quantity, timeliness, effectiveness, independence, and work commitment. This study will also discuss the obstacles faced by the assistants during their duty. This study used a qualitative descriptive method to describe the phenomenon of the performance of Village Facilitators and Local Village Facilitators by conducting observations and interviews with related parties. The results showed that the performance of Village Facilitators and Village Local Assistance in charge was good enough. Keywords: Performance, Village Companion, Local Village Companion, Village Fund